Bandgap Engineering of TiO2 for Enhanced Selectivity in Photoelectrochemical Glycerol Oxidation - Pecoraro, Claudio Maria; Wu, Siming; Santamaria, Monica; Schmuki, Patrik (Advanced Materials Interfaces, 2024)
The application of photoelectrochemical cells to the partial oxidation of biomass represents a promising avenue as a sustainable process for obtaining valuable products. However, achieving both efficient conversion rates and high selectivity of desired products remains a great challenge. In this study, the photoelectrochemical oxidation of glycerol is investigated to produce dihydroxyacetone (DHA) as the primary target using TiO2 nanotubes (NTs) as the photoanode. Nitrogen doping is used to modify the TiO2 NTs, resulting in enhanced visible light photoactivity in N-doped NTs. These N-doped NTs exhibit a high selectivity toward DHA and show a remarkable faradaic efficiency when irradiated with light at a wavelength of 450 nm, i.e., light that excites N-related states in the band gap of TiO2. The N-doped material also exhibits remarkable stability over prolonged reaction periods. The superior performance of N-doped NTs can be attributed to the band-engineering effects induced by nitrogen doping. Specifically, N-doping leads to an upward shift of the valence band, thereby adjusting the exit energy levels of photogenerated holes that result in a high selectivity toward glycerol conversion to DHA.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biomass; N-doping; nanotubes; photoelectrocatalysis; TiO

Platinum single atoms on titania aid dye photodegradation whereas platinum nanoparticles do not - Pecoraro, Claudio Maria; Sopha, Hanna; Wu, Siming; Kim, Hyesung; Wang, Yue; Macak, Jan; Santamaria, Monica; Schmuki, Patrik (Nanoscale, 2025)
The photocatalytic degradation of unwanted organic species has been investigated for decades using modified and non-modified titania nanostructures. In the present study, we investigate the co-catalytic effect of single atoms (SAs) of Pt and Pt nanoparticles on titania substrates on the degradation of the two typical photodegradation model pollutants: Acid Orange 7 (AO7) and Rhodamine B (RhB). For this, we use highly defined sputter deposited anatase layers and load them with Pt SAs at different loading densities or alternatively with Pt nanoparticles. We find that the Pt SAs have strong accelerating effects (already for a low loading density of ∼105 SAs µm−2) on the photodegradation of AO7, whereas Pt nanoparticles do hardly have an effect on the decay kinetics. The main beneficial effect of SA Pt is facilitated superoxide formation, which for SAs is significantly enhanced. Overall, the work demonstrates that Pt SA co-catalysts can have a beneficial effect not only for the well-studied use of H2 generation, but also in the photocatalytic degradation of pollutants—this is particularly the case if the degradation is dominated by a conduction band electron transfer to dissolved O2 in the solution.
CRIS-Team Scopus Importer:2025-02-28